Application Values of Six Scoring Systems in the Prognosis of Stroke Patients - Li, Qun-Xi; Zhao, Xiao-Jing; Fan, Hai-Yan; Li, Xiang-Nan; Wang, Da-Li; Wang, Xiu-Jie; Zhang, Jiang; Chen, Rui-Ying; Zhang, Li (Frontiers in Neurology, 2020)
Objective: The present study aimed to evaluate the prognostic value of Acute Physiology and Chronic Health Evaluation (APACHE; II and III), Chinese Stroke Scale (CSS), National Institutes of Health Stroke Score (NIHSS), activities of daily living (ADL) (Barthel index, BI), and Glasgow Coma Scale (GCS) scores for stroke patients. Methods: A total of 352 stroke patients were evaluated using APACHE II, APACHE III, CSS, NIHSS, ADL, and GCS scores within 24 h after admission. And these patients were consecutive admissions to the hospital. The endpoint was in-hospital death. The scores of these scales were compared between the survival group and death group, and the receiver operating characteristic (ROC) curves were drawn. The ability of each scoring system to predict the prognosis of patients was evaluated using the area under the ROC curve, and the areas under the curves (AUCs) of these six scales were compared. Results: The AUCs of the APACHE II, APACHE III, CSS, NIHSS, ADL, and GCS scores were 0.882, 0.867, 0.832, 0.859, 0.838, and 0.819, respectively. Conclusion: APACHE II, APACHE III, CSS, NIHSS, ADL, and GCS scores have good predictive values in the prognosis of stroke patients. APACHE II is superior among the other five scales.